A case series of children in a UK hospital infected with panton-valentine leucocidin positive Staphylococcus aureus: features of an important emerging infection. (4th April 2011) - Knight, Y; Irving, K; Alexander, E; Fidler, K
Abstract : Aims: To describe the important clinical features and management of cases of Panton-Valentine Leucocidin (PVL) positive Staphylococcus aureus in children in a UK hospital from 2009 to 2010. To highlight the invasive and virulent nature of this emerging infection. Methods: Retrospective review of case notes of six patients attending the hospital between 2009 to 2010 with reference laboratory confirmed PVL positive Staphylococcus aureus infection. Results: Six previously health children were admitted to the hospital with PVL positive Staphylococcus aureus infection. Three cases initially presented with large boils on numerous sites, featuring a characteristic necrotic core. The other three cases presented with joint pain, namely shoulder, knee and hip respectively. Based on history, it is suspected two of the cases may have been acquired from parental exposure as healthworkers; the remaining cases appear to have a community source. The unifying feature of all six cases was the long treatment course required, with varying combinations of intravenous flucloxacillin, cephalosporin, clindamycin or rifampicin. The shoulder and knee joint infections required multiple surgical washouts and an average of 6 weeks intravenous antibiotic treatment to achieve resolution. One case presenting with boils developed a PVL positive chest wall abscess, requiring multiple courses of intravenous antibiotic treatment and prolonged chest drainage. Conclusions: Children infected with PVL positive staphylococcus aureus often develop musculoskeletal involvement requiring surgical intervention and prolonged intravenous antibiotic treatment. Early recognition of the characteristic necrotic core boils would aid early diagnosis. Raising awareness of this virulent emerging infection is an important strategy to minimising its spread.